Talent management in SMEs: An exploratory study of Polish companies - Urban Pauli; Aleksy Pocztowski (Entrepreneurial Business and Economics Review (EBER), 2019)
Objective: The main goal of the study is to identify and map practices of TM in SMEs and search for common patterns. The main questions during the design of the research were: How do SMEs define talent and what are its indicators? What is the approach to TM in SMEs? What kind of activities relating to TM do SMEs undertake? Is it possible to link activities undertaken by SMEs in coherent patterns? Research Design & Methods: This exploratory study was conducted on a randomly selected 200 Polish SMEs. After collecting the sample, we employed the CAPI technique. Most of the questions were open-ended and multiple-choice. In the analysis, we used data clustering and descriptive statistics. Findings: The research confirms that talent management in SMEs occurs in various ways, while particular approaches differ significantly. However, taking into account such categories as talent indicators, main activities undertaken, talents' tasks and roles, we can identify some common patterns. Implications & Recommendations: The main implication is that a variety of approaches to TM in SMEs requires the application of a contextual framework, which should include the specificity of both internal and external factors. We recommend SMEs' owners and managers define the main aim of introducing TM practices and shape them in a way that allows fulfilling expected outcomes. Contribution & Value Added: This paper addresses three main research gaps. By presenting data gathered from 200 SMEs we refer to a call for empirically grounded studies. By conducting cluster analysis and developing a model, we refer to the lack of conceptual frameworks of TM in SMEs. Finally, we address a call for more context-specific research by presenting data on TM practices in Polish SMEs.
Keywords: M51; M54; 330; talent; talent management; SMEs; human resource management